1982
DOI: 10.1111/jzo.1982.197.4.559
|View full text |Cite
|
Sign up to set email alerts
|

The breeding biology of magpies Pica pica in an urban environment

Abstract: The colonisation of British cities by magpies is a recent phenomenon. This work presents an analysis of magpie breeding biology in the urban environment of south Manchester; laying date, nesting success, clutch size, incubation period, hatching success and nestling success have been investigated and where possible, are contrasted with the situation in rural areas. A proportion of magpies in Manchester renovate an old nest for the breeding attempt, a habit which is uncommon in rural populations. As a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 11 publications
3
62
1
Order By: Relevance
“…Jerzak [32] found in Zielona Góra, Poland, a positive correlation between the distribution of the Magpie breeding pairs and tree density. Similar observations were done in Manchester, UK, by Tatner [50] and in Lvov, Ukraine by Bokotey [8]. Birkhead et al [7] in Sheffield, UK, found also that the Magpie density was related to/depended on the distribution of suitable nesting sites (high trees).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Jerzak [32] found in Zielona Góra, Poland, a positive correlation between the distribution of the Magpie breeding pairs and tree density. Similar observations were done in Manchester, UK, by Tatner [50] and in Lvov, Ukraine by Bokotey [8]. Birkhead et al [7] in Sheffield, UK, found also that the Magpie density was related to/depended on the distribution of suitable nesting sites (high trees).…”
Section: Discussionsupporting
confidence: 68%
“…In Manchester, UK, about 38% nests were in Populus sp. [50], 44% nests in Zielona Góra, Poland, [32], and 49% in Cracow, Poland [5]. Many other authors describe that the Magpies often build nests in Populus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Tatner 1982;Dhondt et al 1984;Bowman et al 1998). Thus, the general phenomenon of an earlier breeding season in urban ecosystems can not be explained by a reduced migratory disposition.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive explanations for non-parental infanticides involve direct exploitation (using offspring as food), sexual selection (mate replacement), and resource competition (access to food, nest site, territory, etc.). Although magpies are known to consume eggs and offspring of passerine birds, including suspected predation on their own species (Tatner 1982;Jerzak 2002), the perpetrator did not consume any part of the body of the nestlings during the attacks, and the nestlings were found dead under the nest without any signs of being eaten. Thus, we can exclude the exploitation hypothesis as the explanation for this case of infanticide.…”
Section: Discussionmentioning
confidence: 99%